Biased self‐perceptions of social competence and engagement in physical and relational aggression: The moderating role of peer status and sex. Issue 6 (24th July 2014) - McQuade, Julia D.; Achufusi, Adaora K.; Shoulberg, Erin K.; Murray‐Close, Dianna
<x xml:space="preserve">Abstract</x> This study sought to expand on prior research suggesting that children low in peer status who either over‐ or underestimate their social competence relative to others' reports are more likely to be aggressive (White and Kistner [2011]. Journal of Abnormal Child Psychology, 39, 645–656). The curvilinear associations between social competence bias and two forms of aggression (physical and relational) were examined in a sample of 4th through 6th graders (n = 183); moderation by both sex and peer status (peer preference and popularity) also were tested. Social competence bias was operationally defined as the residual difference between child and teacher ratings of the child's social competence. Aggression and peer status were measured using peer nomination procedures. There was a significant curvilinear association between social competence bias and physical aggression moderated by both types of peer status. For low peer status children greater underestimation and overestimation of social competence was associated with higher physical aggression. The curvilinear association between social competence bias and relational aggression was moderated by both peer status and sex. Popular boys had higher rates of relational aggression when they had accurate, rather than biased, self‐perceptions of social competence. However, for very highly preferred girls, a more extreme positive bias was associated with an exponential increase in relational aggression. Results are discussed in terms of implications for aggression theory and intervention. Aggr. Behav. 40:512–525, 2014. © 2014 Wiley Periodicals, Inc.